2021
DOI: 10.1016/j.jiac.2021.02.018
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of clinical efficacy of ribavirin in adults hospitalized with severe COVID-19

Abstract: Introduction Coronavirus disease-2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) swept rapidly throughout the world. So far, no therapeutics have yet proven to be effective. Ribavirin was recommended for the treatment of COVID-19 in China because of its in vitro activity. However, evidence supporting its clinical use with good efficacy is still lacking. Methods A total of 208 confirmed severe COVID-19 patients who were hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“… [17] , [86] , [88] , [102] , [122] , [130] Studies reporting inefficacy of IFNα or delayed hospital discharge also reported a longer time from the onset of symptoms to hospital admission. [46] , [69] Based on these studies, we believe that the magic number is five. Treatment initiated within five days of the onset of symptoms may be considered as early treatment, which confers a better treatment response and prognosis.…”
Section: Interferon Alpha Treatment For Covid-19 Patients In the Current Contextmentioning
confidence: 87%
See 3 more Smart Citations
“… [17] , [86] , [88] , [102] , [122] , [130] Studies reporting inefficacy of IFNα or delayed hospital discharge also reported a longer time from the onset of symptoms to hospital admission. [46] , [69] Based on these studies, we believe that the magic number is five. Treatment initiated within five days of the onset of symptoms may be considered as early treatment, which confers a better treatment response and prognosis.…”
Section: Interferon Alpha Treatment For Covid-19 Patients In the Current Contextmentioning
confidence: 87%
“…A total of 178 studies were found to have reported IFNα treatment for COVID-19 (Supplemental 2). [13] , [17] , [19] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , …”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsunclassified
See 2 more Smart Citations
“…Recently, ribavirin was recommended to be used with interferon α or lopinavir-ritonavir for COVID-19 treatment. However, the effects of ribavirin on COVID-19 are controversial and need to be further confirmed [ 35 ]. Recently, a molecular docking result indicated that sofosbuvir may inhibit RNA-dependent RNA polymerase (RdRP) of SARS-CoV-2 [ 36 ].…”
Section: Drug Repurposing For Covid-19mentioning
confidence: 99%